Review on distribution, fate, and management of potentially toxic elements in incinerated medical wastes. (15th March 2023) - Bolan, Shiv; Padhye, Lokesh P.; Kumar, Manish; Antoniadis, Vasileios; Sridharan, Srinidhi; Tang, Yuanyuan; Singh, Narendra; Hewawasam, Choolaka; Vithanage, Meththika; Singh, Lal; Rinklebe, Jörg; Song, Hocheol; et al.
Abstract: Medical wastes include all solid and liquid wastes that are produced during the treatment, diagnosis, and immunisation of animals and humans. A significant proportion of medical waste is infectious, hazardous, radioactive, and contains potentially toxic elements (PTEs) (i.e., heavy metal (loids)). PTEs, including arsenic (As), cadmium (Cd), lead (Pb) and mercury (Hg), are mostly present in plastic, syringes, rubber, adhesive plaster, battery wastes of medical facilities in elemental form, as well as oxides, chlorides, and sulfates. Incineration and sterilisation are the most common technologies adopted for the safe management and disposal of medical wastes, which are primarily aimed at eliminating deadly pathogens. The ash materials derived from the incineration of hazardous medical wastes are generally disposed of in landfills after the solidification/stabilisation (S/S) process. In contrast, the ash materials derived from nonhazardous wastes are applied to the soil as a source of nutrients and soil amendment. The release of PTEs from medical waste ash material from landfill sites and soil application can result in ecotoxicity. The present study is a review paper that aims to critically review the dynamisms of PTEs in various environmental media after medical waste disposal, the environmental and health implications of their poor management, and the common misconceptions regarding medical waste. Graphical abstract: Image 1 Highlights: Safe management of hazardous medical wastes is a major global challenge. A significant proportion of medical waste is infectious, hazardous and radioactive. Potentially toxic elements (PTEs) in medical waste occur mostly as oxides. Incinerated medical waste ash application can release PTEs to environment. Chemical stabilisation is effective in preventing PTEs release into the environment.